Antibacterial Properties of Calcium Fluoride-Based Composite Materials: In Vitro Study. (8th December 2016) - Łukomska-Szymańska, Monika; Zarzycka, Beata; Grzegorczyk, Janina; Sokołowski, Krzysztof; Półtorak, Konrad; Sokołowski, Jerzy; Łapińska, Barbara
Abstract : The aim of the study was to evaluate antibacterial activity of composite materials modified with calcium fluoride against cariogenic bacteria S. mutans and L. acidophilus . One commercially available conventional light-curing composite material containing fluoride ions (F2) and two commercially available flowable light-curing composite materials (Flow Art and X-Flow) modified with 1.5, 2.5, and 5.0 wt% anhydrous calcium fluoride addition were used in the study. Composite material samples were incubated in 0.95% NaCl at 35°C for 3 days; then dilution series of S. mutans and L. acidophilus strains were made from the eluates. Bacteria dilutions were cultivated on media afterwards. Colony-forming unit per 1 mL of solution (CFU/mL) was calculated. Composite materials modified with calcium fluoride highly reduced (p < 0.001 ) bacteria growth compared to commercially available composite materials containing fluoride compounds. The greatest reduction in bacteria growth was observed for composite materials modified with 1.5% wt. CaF2 . All three tested composite materials showed statistically greater antibacterial activity against L. acidophilus than against S. mutans .